2007
DOI: 10.1017/s104161020700511x
|View full text |Cite
|
Sign up to set email alerts
|

Potential ethnic modifiers in the assessment and treatment of Alzheimer's disease: challenges for the future

Abstract: Greater participation of ethnically diverse participants in clinical trials for AD would generate additional information on possible differences in metabolism, treatment response, adverse events to therapeutic agents, and could foster the investigation of genetic variability among ethnic groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
57
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(60 citation statements)
references
References 57 publications
2
57
0
Order By: Relevance
“…Minority patients are more likely receive care from nonspousal family members [16,17]; have less access to medical care and lower rates of AD medication use [18,19]; and have lower participation rates in AD clinical trials [20]. In NACC, a larger proportion of minority patients exists among the nonspousal caregiver-patient dyads and these patients less commonly took AD medications.…”
Section: Discussionmentioning
confidence: 99%
“…Minority patients are more likely receive care from nonspousal family members [16,17]; have less access to medical care and lower rates of AD medication use [18,19]; and have lower participation rates in AD clinical trials [20]. In NACC, a larger proportion of minority patients exists among the nonspousal caregiver-patient dyads and these patients less commonly took AD medications.…”
Section: Discussionmentioning
confidence: 99%
“…In the year 2000, researchers from the National Institute on Aging, the Alzheimer's Disease Cooperative Study and pharmaceutical companies reviewed their clinical trials' data to ascertain the number of non-white subjects in their clinical trials for AD. An analysis of this large comprehensive data set of subjects recruited into clinical research programs indicated that non-whites represented only 3.6% of the total population studied [6] . This analysis demonstrated that the number of non-white subjects was insufficient to investigate possible ethnic differences in treatment response and adverse events.…”
Section: Introductionmentioning
confidence: 99%
“…1 An analysis of data gathered by researchers for the National Institute on Aging, the Alzheimer Disease Cooperative Study, and pharmaceutical companies revealed that only 3.6% of the sample population represented non-white subjects. 2 This lack of participation has been attributed to a variety of factors that include a mistrust of the predominately white research establishment with its well-documented history of medical abuse, differing cultural attitudes and beliefs towards research and illness, isolation of older individuals, and a lack of education about the purpose of research in general and the informed consent process in particular. 1, 35 …”
mentioning
confidence: 99%